Work Discipline and Job Satisfaction as Determinants of Employee Performance: Evidence from the Department of Industry, Trade, Energy, and Mineral Resources in Medan - Nainggolan, Debora Marina Rutina; Sagala, Maduma Sari; Bako, Evi Novalin (Global Insights in Management and Economic Research, 2025)
Introduction: Employee performance fluctuation remains a critical challenge in public sector organizations, particularly in developing countries where administrative effectiveness directly impacts regional economic development. Purpose of the study: This research investigates the influence of work discipline and job satisfaction on employee performance at the Department of Industry, Trade, Energy, and Mineral Resources in Medan, Indonesia. Materials and methods: A quantitative approach was employed using saturated sampling of 66 civil servants. Data were collected through validated questionnaires and analyzed using multiple linear regression analysis. Results: The findings revealed that work discipline (t = 3.722, p < 0.05) and job satisfaction (t = 4.194, p < 0.05) significantly and positively influence employee performance. The regression model (Y = 9.102 + 0.261X₁ + 0.281X₂) demonstrated statistical significance (F = 20.237, p < 0.001), with both independent variables explaining 37.2% of the variance in employee performance. Conclusions: Work discipline and job satisfaction are critical determinants of employee performance in public sector organizations. Management should prioritize strengthening disciplinary mechanisms and enhancing job satisfaction to optimize organizational effectiveness.